Laser-driven direct synthesis of carbon nanodots and application as sensitizers for visible-light photocatalysis. (January 2020) - Mas, Nuria; Hueso, Jose L.; Martinez, Gema; Madrid, Ainhoa; Mallada, Reyes; Ortega-Liebana, M. Carmen; Bueno-Alejo, Carlos; Santamaria, Jesus
Abstract: We present the first successful synthesis of monodisperse carbon nanodots (CNDs) with tunable photoluminescence (PL) carried out by laser pyrolysis of two common volatile organic precursors such as toluene and pyridine. Remarkably, the initial chemical composition of the precursor determines the formation of undoped or N-doped CNDs and their corresponding absorption response in the visible range (expanded for the latter). We demonstrate the control and versatility of this synthesis method to tune the final outcome and its potential to explore a great number of potential solvent candidates. Furthermore, we have successfully exploited these CNDs (both undoped and N-doped) as effective sensitizers of TiO2 nanoparticles in the visible-light driven photo-degradation of a cationic dye selected as model organic pollutant. Graphical abstract: Image 1